Rorgo Fretellus and the two redactions of Descriptio de locis sanctis (ACME, 2024)
This paper presents and discusses the poor biographical data available on Rorgo Fretellus, the author of a successful topography of the Holy Land, dated back to the first half of the 12th century (Descriptio de locis sanctis). It also offers an overview of the two known redactions of the Descriptio, framing the main aspects related to their manuscript tradition, their reception and their publishing history. While the first redaction, dedicated to the Bohemian bishop Henry Sdyck, is preserved in six codices, the second, which is destined for the Spanish earl Rodrigo of Toledo and whose Fretellian authorship is discussed and confirmed in this paper, enjoyed greater success: it is transmitted by forty-two witnesses and constitutes the source of subsequent geographical works regarding the Holy Land. A comparison of the critical texts of the two prologues is provided in the appendix, in order to offer an insight into the changes made from the first to the second version of the Descriptio.
Keywords: Rorgo Fretellus; Holy Land; Pilgrimage; Geography; Authorial Versions